Islam Jawa: Antara Holisme dan Individualisme - AG., Muhaimin (Studia Islamika, 2005)
this book is a continuation of the writer's previous work, From Cosmogony to Exorcism in a Javanese Genesis; the Spirit Seed (2000), in which he discussed how mythological beliefs regarding the origin and creation of the world pleyed an important role in the social and religious lives of the Javanese. These mythological beliefs constituted the basis of the formation of both social relations within the Javanese community, as well as the ritual practices of the Javanese in seeking fortune and safety (slametan)DOI:Â 10.15408/sdi.v12i1.649